Rationalism in Harun Nasution’s Epistemology of Islamic Law - Zaid Hamdani; Mohammad Taufiq Rahman (Parahyangan Catholic University, 2022)
The term 'epistemology' is a term directly related to the field of philosophical debate. As one of the branches of philosophy, it studies science in terms of its definition, the establishment of its types, the determination of its sources and channels and the identification of its limits and limitations. Although these epistemological questions are commonly used in the disciplines of philosophy and the sciences, for some scholars they are also relevant and useful in the field of Islamic law. The following brief study will attempt to elaborate on the epistemological theory of Islamic law by analyzing the thoughts of a prominent Islamic scholar, Harun Nasution, an expert in Islamic philosophy and theology.